(untitled) (Interdisciplinary Studies Journal, 2025)
This is a theoretical-affective text in homage to the life and work of the Argentine María Lugones, a seminal figure in decolonial thought and perspective, who passed away in July 2020. Its aim is to present the philosophical and epistemological foundations of her work through an immersion in her experience as a woman of color, lesbian, wanderer, decolonial feminist philosopher, critical theorist, Chicana university professor in the U.S. academy, popular educator, and singer, as well as an excellent host, according to friends and family. Her journey through academia and popular education is traced here, with emphasis on her rich philosophical thought, from which concepts such as world-traveling, pilgrimage, modern-colonial gender system, coloniality of gender, and fractured locus, among many others, emerged. Far from intending to exhaust the author’s vast body of work, this study employed a methodology of critical literature review, highlighting two key texts: "Heterosexualism and the Colonial/Modern Gender System" (2008) and "Toward a Decolonial Feminism" (2014). Through her fused way of thinking, she offers philosophical means to understand the differences between human beings and between humans and their environments, in ways that allow us to grasp from which worldview they perceive the world—whether locally or globally. In other words, beyond Lugones’s contribution to feminist philosophical thought, particularly through her reflections on intersectionality and its deep roots in the coloniality of power, knowledge, and being, lies her unwavering commitment to understanding the lived experiences of women in diverse cultural contexts, under the influence of these forms of coloniality. With this writing, the intention is not only to systematize María Lugones’s main ideas but also to honor her memory—calling on those who resonate with her writing of love to never forget her.